Reactivity and Morphology of Oxygen-Modified Au Surfaces - Baber, Ashleigh E. (2012)
Inducing the adsorption of oxygen on gold surfaces transforms the inert metal into a surprisingly reactive material, which acts as a highly selective, low-temperature catalyst. The strong interaction of atomic oxygen with Au greatly affects the surface morphology by increasing the number of undercoordinated Au atoms and lifting the surface reconstruction. Through the combination of experimental and theoretical techniques, we have fully characterized an oxygen-modified Au(100) surface and determined the structure–reactivity relationship of O–Au species. Bulk-implanted oxygen does not affect the reactivity of Au surfaces and subsurface oxygen is found to be unstable. Oxygen stabilizes undercoordinated Au atoms on the surface and becomes highly active for oxidation reactions when adsorbed on unreconstructed Au(100) sites.